Pronghorn and cattle at Playa - Sprague, Sallie, photographer (Colorado State University. Libraries, 2008)
Cattle grazing on playa with pronghorn walking along hill in foreground, just over the crest.
Keywords: cattle; SGS; pronghorn; animals